ANALISIS PENDAPATAN DAN PERLINDUNGAN HAK-HAK BURUH TANI HARIAN LEPAS (BTHL) DI KAB. KARO SUMATERA UTARA - Rosmawati Br. Bangun; Matius Bangun (Jurnal Darma Agung, 2021)
This study aims at seeing and learning the income of the Daily Lepas Farmer (BTHL) as well as the protection carried out by the Regional Government for the BTHL. This research was carried out in Berastagi Subdistrict, Karo Regency and the method used is qualitative by collecting data from interviews, field observations, literary studies, mass media, and documentation.The results of the research show that the income levels of Vegetable Farmers () BTSy, Fruit Farmers (BTBb) and Flower Farmers (BTBg) show differences that are not too high. The average result, BTSy income is Rp. 2,375,000 - BTBb of Rp. 2,556,700, - BTBg of Rp. 2,450,762, - (rounding off). The BTSy average income is Rp. 2,375,000, - (100.00) which consists of Main income of Rp. 1,800,750, - (75.82%), from the main part-time additional income of Rp. 410,000, - (17.26%) and part-time income of Rp. 164,245, - (06.92%).The average BTBb income source is Rp. 2,556,700, - (100.00) which consists of main income of Rp. 2,236,601, - (87.48%), the main part-time income of Rp. 231,669, - (09.06%) and non-agricultural side income of Rp. 111,570, - (04.37%) BTBg revenue of Rp. 2,450,762, - (100.00) consisting of Main income of Rp. 2,001,924, - (81.69%), income from main part time Rp. 331,669, - (13.53%) and side income from outside agriculture is Rp. 117,169, - (04.78%).The protection that is carried out by the Karo Regency Government for casual daily laborers in accordance with Article 99 (1) is only implemented in the Family Planning service while Child Care and the creation of a Labor Settlement are only at the planning stage. Protection as referred to in Law Number 24 of 2011 concerning Social Security Administering Bodies (BPJS), both Health Insurance and Employment Security for Casual Daily Farm Workers (BTHL) who work for companies and have not regulated BRHL working in individual or household businesses.